Germline copy number variants in RUNX1: An updated case report and a decade-old red herring - Natalie T. Deuitch; Amra Kajdic; Erica Bresciani; Marshall S. Horwitz; Hamish S. Scott; Katie Craft; Shawn Chong; David J. Young; Lucy A. Godley; Paul P. Liu (BJC Reports)
Abstract Pathogenic/likely pathogenic (P/LP) germline variants in RUNX1 cause familial platelet disorder with associated myeloid malignancies (FPDMM), also known as RUNX1-Familial Platelet Disorder (RUNX1-FPD, or FPD), a condition characterized by qualitative and quantitative platelet defects and predisposition to hematopoietic malignancies. Here, we present follow up to a case of a woman with acute myeloid leukemia and lifelong thrombocytopenia which had previously been attributed to presumptive pathogenic (P) GATA2 missense variants. However, re-evaluation with updated molecular technology sensitive for detection of copy number variants (CNVs) led to the identification of a P deletion of exons 5-6 in RUNX1, which had been undetected when examined at first presentation. This case highlights the importance of comprehensive molecular evaluation and careful variant interpretation, especially regarding CNVs.